Taking advantage of genomic data to develop reliable microsatellite loci in Trypanosoma brucei - Sistrom, Mark; Echodu, Richard; Hyseni, Chaz; Enyaru, John; Aksoy, Serap; Caccone, Adalgisa (Molecular Ecology Resources, 2013)
Taking advantage of the annotated genome of Trypanosoma brucei, a unicellular eukaryotic parasite which causes sleeping sickness across sub3Saharan Africa, this study develops 11 variable microsatellite loci, which reliably amplify in poor and unknown quality DNA samples. We provide insights into effective screening methods to develop microsatellite loci from genomic resources and a set of markers to study regional population variation in this important parasite.
Keywords: Microsatellites; Population genetics; Pathogens; Africa